2018
DOI: 10.1039/c8lc00357b
|View full text |Cite
|
Sign up to set email alerts
|

Microphysiological flux balance platform unravels the dynamics of drug induced steatosis

Abstract: Drug development is currently hampered by the inability of animal experiments to accurately predict human response. While emerging organ on chip technology offers to reduce risk using microfluidic models of human tissues, the technology still mostly relies on end-point assays and biomarker measurements to assess tissue damage resulting in limited mechanistic information and difficulties to detect adverse effects occurring below the threshold of cellular damage. Here we present a sensor-integrated liver on chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…Another study by Ehrlich et al developed a sensor‐integrated liver on chip array using human liver organoids composed of albumin‐positive E6/E7LOW hepatocytes and endothelial cells, monitoring oxygen while glucose, lactate, and temperature were measured in real time using microfluidic electrochemical sensors. Although the study showed that lipid accumulation is not a result of increased production but rather suppression of fatty acid oxidation, their platform did not focus on steatosis . An in vitro liver model was engineered by Feaver et al by coculturing PHHs, hepatic stellate cells, and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Ehrlich et al developed a sensor‐integrated liver on chip array using human liver organoids composed of albumin‐positive E6/E7LOW hepatocytes and endothelial cells, monitoring oxygen while glucose, lactate, and temperature were measured in real time using microfluidic electrochemical sensors. Although the study showed that lipid accumulation is not a result of increased production but rather suppression of fatty acid oxidation, their platform did not focus on steatosis . An in vitro liver model was engineered by Feaver et al by coculturing PHHs, hepatic stellate cells, and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the emerging organ‐on‐chip (OoC) technology can be the real game‐changer: these platforms represent dynamic cell culture systems that offer great promise for simulating and studying human diseases (Liu et al, 2019; Rothbauer et al, 2019), including NAFLD, at the tissue and organ level (Bovard et al, 2018; Chang et al, 2017; Li, George, Vernetti, Gough, & Taylor, 2018; Lu et al, 2018). Recently, our group and others (Bulutoglu et al, 2019; Ehrlich et al, 2018; Gori et al, 2016; Lee & Sung, 2018) have proposed alternative and more complex models of hepatic steatosis in a microfluidic chip to overcome the bottlenecks and limitations of the canonical in vitro cell culture models.…”
Section: Introductionmentioning
confidence: 99%
“…A liver-on-a-chip with four sensors to measure oxygen, lactate, glucose, and temperature was used to estimate central drug flux to determine the mechanism of injury of valproate and stavudine. (32) Both drugs led to dose-dependent damage attributed to lipid accumulation in this translational demonstration. The lack of a multicellular architecture makes it unclear whether these devices can mimic the mechanism and toxicological endpoints of in vivo responses to drugs.…”
Section: Diseasementioning
confidence: 64%
“…A liver‐on‐a‐chip with four sensors to measure oxygen, lactate, glucose, and temperature was used to estimate central drug flux to determine the mechanism of injury of valproate and stavudine . Both drugs led to dose‐dependent damage attributed to lipid accumulation in this translational demonstration.…”
Section: Liver Disease‐on‐a‐chip Modelsmentioning
confidence: 93%